Platycodon grandiflorum Triggers Antitumor Immunity by Restricting PD-1 Expression of CD8+ T Cells in Local Tumor Microenvironment - Yang, Ruijie; Pei, Tianli; Huang, Ruifei; Xiao, Yue; Yan, Jiangna; Zhu, Jinglin; Zheng, Chunli; Xiao, Wei; Huang, Chao (Frontiers in Pharmacology, 2022)
In the tumor microenvironment (TME), the activation of programmed death-1 (PD-1) - programmed death ligand-1 (PD-L1) pathway is one of the main signals of immune escape and tumor deterioration. Clinically, application of monoclonal antibodies slows down the progression of various malignancies and prolongs the survival of patients effectively. However, these treatment result in serious immune-related adverse events (irAEs) owning to systemic immune activation. Therefore, achieving long-term therapeutic effects and low side effects, it is necessary to find drugs inhibiting the local PD-1/PD-L1 signaling pathway of TME. Here, we discovered that Platycodon grandiflorum (PG), a medicine food homology herb, reduced the expression of PD-1 on the surface of CD8+ T cells to exert anti-tumor effects in NSCLC. Firstly, combining systems pharmacology strategies and clinical data analysis, we found that PG has the potential to immunomodulate T cells and suppress tumors. Secondly, in vivo and in vitro experiments confirmed the anti-tumor effect of the combination of PlatycodinD and PlatycodinD3, which are preferred and representative compounds. Mechanistically, PG increased the infiltration and killing activity of CD8+ T cells, which was related to the decrease of PD-1+ CD8+ T cells. Furthermore, we confirmed that PG regulated the expression of PD-1 on the surface of CD8+ T via reducing the secretion of VEGF-A regulated by the level of P-STAT3 in tumor cells. Additionally, PG also positively impacted the biological processes downstream of STAT3. Overall, we demonstrated that PG-mediated down-regulation of PD-1 on the surface of CD8+ T cells represents a promising strategy to locally enhance T cell responses and improve anti-tumor immunity.